Effect of Electronic Word Of Mouth, Product Quality, and Price on Purchase Intention - Tasya Amanda; Hery Winoto Tj; Aini Kusniawati; Surachman Surjaatmadja (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study was conducted to analyze the effect of Electronic Word Of Mouth, Product Quality, and Price on purchase intention. This research was conducted on the Imokey.Id Brand on the Instagram Platform with a sample of 100 respondents from imokey.id followers. This study uses a verification research model with an explanatory survey method, namely the research method for collecting sample data using slovin calculations. This study has the result that electronic word of mouth has an influence on purchase intention while product quality does not have a direct influence on purchase intention and price has an influence on purchase intention.